PENINGKATAN HASIL BELAJAR PESERTA DIDIK MATERI PENYAJIAN DATA MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN GOOGLE SITES DI KELAS IVB SDN 27 ANAK AIR - Tri Manza, Sanesa; Safitri Syam, Salmaini; Sherlyane Hendri; Syafri Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of students in the topic of data presentation. In addition, the learning process had not been fully guided by the Deep Learning Lesson Plan (Rencana Pelaksanaan Pembelajaran Mendalam/RPPM). Classroom instruction remained predominantly teacher-centered, the learning media used were not yet interactive, and innovative and varied learning models had not been optimally implemented. Therefore, this study aimed to describe the improvement of students' learning outcomes in the topic of data presentation through the implementation of the Problem Based Learning (PBL) model assisted by Google Sites in Class IVB of SDN 27 Anak Air. This research employed a Classroom Action Research (CAR) design using both qualitative and quantitative approaches. The study was conducted in two cycles. Cycle I consisted of two meetings, while Cycle II consisted of one meeting. Each cycle comprised four stages: planning, implementation, observation, and reflection. The research subjects were the teacher and 27 students of Class IVB at SDN 27 Anak Air.The results showed improvements in several aspects: (a) the quality of the Deep Learning Lesson Plan (RPPM) increased from 96.42% (Very Good) in Cycle I to 100% (Very Good) in Cycle II; (b) the implementation of learning improved from 82.14% (Good) to 96.42% (Very Good) in the teacher aspect and from 82.14% (Good) to 96.42% (Very Good) in the student aspect; and (c) students' learning outcomes improved in all assessed domains. The average score for the attitude aspect increased from 71.82 in Cycle I to 82.41 in Cycle II. The average knowledge score increased from 74.25 to 87.33, while the average skills score increased from 74.61 to 84.85. Based on these findings, it can be concluded that the implementation of the Problem Based Learning (PBL) model assisted by Google Sites effectively improved students' learning outcomes in the topic of data presentation in Class IVB of SDN 27 Anak Air.